A autoavaliação institucional na Escola Municipal Estudante Emmanuel Bezerra: construindo uma dinâmica de participação - Oliveira, Larissa Fernanda dos Santos (2014)
This project was based on an implemented investigation of the institutional self-evaluation at Municipal Emmanuel Bezerra school, located at the west zone of Natal capital in Rio Grande do Norte state, where school individuals were analysed in interaction. A qualitative research was taken under the use of several pieces of information and collected out of several sources, such as: managing, docent and administrative staff interviews; present school legislation, political pedagogical project, scholar regiment as well as the 2013 action plans documental analyses; and the literature review focused in books and articles which treats of evaluation, State Evaluator and the public educational politics in order to promote the dialogue between school theory and reality. The institutional evaluation has been the theme debated through several studies. However, with its major focus on the evaluation systems and High Education aiming to raise competition having implying the reaching of educational quality as justification under liberal view. Notwithstanding, over the controlling function of the educational results and competition trigger amongst the educational institutions to the accruement of the received resources, it is believed that this institutional evaluation, however the system, can assist in the educational services improvement offered to the local public, when endeavoured to the purpose of supporting human development. Having the obtained data, the self-evaluation process implemented at the concerned school, the conceptions which permeate the school environment as well as the community joining given in this object lesson, was described and analysed as dialoguing with the political pedagogical project and comprehending the constitution in a democratic management